Performance and Impact of Front Line Demonstration of Papaya in Western Rajasthan: FLD’S OF PAPAYA IN WESTERN RAJASTHAN - kumar, chandan; M.K. Choudhary; A. S. Tetarwal; B R Kuri (Annals of Arid Zone, 2024)
Papaya (Carica papaya) is a “wonder fruit of the tropic” has become a popular due to its fast growth, short gestation period, high nutrient and medicinal value as well as high productivity. India leads the world (31.51%) in papaya production with an annual output of about 5.75 million tonnes (NHB, 2022) in the 0.15 million hectare and the national average productivity of papaya is 44.86 mt/ha but in Rajasthan it was 14.93 mt/ha (Anonymous, 2020) which was due to farmers were facing some problems included biotic and abiotic stresses in this arid zone, including these problems lack of technical knowledge of the farmers about judicious and timely implementation of the management strategies against the major biotic stresses (pest and diseases) was important factors to which ultimately reduce its return. Due to dioeciously nature (only 50-60% plants bear fruit), less susceptibility to pest and diseases and inferior quality of local cultivars the papaya grower facing a lot of difficulties. To resolve this problem, the front line technology demonstrations on Papaya Red-lady variety was carried out and show the difference between farmer practice and improved practices. The outcome of present study was, the Red-Lady variety with improved production practices of papaya recorded the average higher yield (71.05 tonnes/ha) as contrast to farmers practices (43.25 tonnes/ha) conventionally acquire by the farmers. Nearly 64.37 per cent rise in the yield over farmers exercise was observed with the highest net return (Rs/ha 7,65,868) and benefit cost ratio (3.55), this variety has made a considerable contribution and brought smile on many faces of papaya grower in the Pali district under II B western zones of Rajasthan.